Analisis Yuridis Kedudukan Istri dari Cucu Pewaris untuk Memperoleh Hak Waris Melalui Wasiat Wajibah - Dinda Gheanisyatara Shafira Putri; Armiwulan Armiwulan; Utiyafina Mardhati Hazhin (Indonesian Journal Publisher, 2026)
This study analyzes the juridical status of the wife of a testator’s grandson in obtaining inheritance rights through the mechanism of wasiat wajibah (mandatory will) under Indonesian Islamic inheritance law. The issue arises from the absence of explicit provisions in the Compilation of Islamic Law (KHI) regulating the granting of a mandatory will to parties beyond adopted children and adoptive parents, leading to divergent judicial interpretations. This research employs a normative juridical method with a descriptive-analytical approach, examining statutory regulations, Islamic legal doctrine, and relevant court decisions, particularly the Decision of the Pemalang Religious Court Number 1313/Pdt.G/2023/PA.Pml. The findings demonstrate that the wife of the testator’s grandson does not qualify as an heir due to the absence of direct blood (nasab) or marital ties with the testator. Consequently, the extension of wasiat wajibah to this party lacks a firm normative foundation in both positive law and classical Islamic jurisprudence. Substantively, the legal reasoning in the examined decision more accurately reflects the concept of munāsakhat (sequential inheritance), whereby inheritance rights of a predeceased husband are transmitted to his heirs, including his wife. This study concludes that legal protection for such parties should be grounded in a clearer doctrinal framework, and calls for reformulation within the KHI to ensure legal certainty while upholding substantive justice in Islamic inheritance adjudication.